Identifying the Factors Affecting the Risk Aversion of Individuals in Iran - Habib Morovat; Syrous Omidvar; Roya Eskandary (فصلنامه پژوهش‌های اقتصادی ایران, 2023)
Risk and uncertainty are key factors in making economic decisions. Since individual attitudes towards risk can greatly influence choices, it is crucial to understand the determinants of such preferences in order to predict and comprehend individuals’ behavior. The present study aimed to investigate the impact of several factors on individuals’ attitudes towards risk, specifically the degree of risk aversion, by examining individuals’ optimism and patience (time preference). The study used a questionnaire to collect data from a sample of 304 individuals in Iran selected through random sampling. The research method was a multivariate regression model. The findings indicated that both optimism and income have a significant negative effect on risk aversion, while age has a significant positive effect. Furthermore, the study found that patience does not have a significant impact on risk aversion.IntroductionRisk and uncertainty are critical factors that heavily influence most economic decisions, including investment, education, employment, and the decision to buy a house or insurance. Such decisions involve an element of risk, so they are highly influenced by individuals’ attitudes towards risk. In developing countries, such as Iran, most individuals typically experience unstable incomes, limited access to insurance, and possess few assets to cushion the impact of severe economic shocks. As a result, individuals in these circumstances are more exposed to risk, and these factors can significantly influence their attitudes towards risk. Understanding the determinants of these preferences is crucial to comprehending and predicting people’s behavior, as different attitudes towards risk lead to different choices. The present study was to examine how certain factors, such as optimism and patience (time preference rate), influence individuals’ attitudes towards risk. In addition, socio-economic variables were included as control variables to account for their potential impact.Materials and MethodsTo gather data on individuals’ degrees of risk aversion, optimism, and patience, this study used a questionnaire based on internationally recognized surveys. The model was then estimated by the general multivariate regression through the ordinary least squares (OLS) method.Results and DiscussionThe descriptive information related to demographic variables is presented in Table 1.  Table 1:  Frequency distribution of demographic sVariableVariable levelFrequencyRelative FrequencyGenderMale15549Female16051Total315100Marital statusSingle21970Married9630Total315100AgeLess than 20 years165Between 20-30 years17255Between 30-40 years10032Above 40 years278Total315100Level of educationHigh school41Diploma–BA9931BA–MA13944MA–PhD7323Total315100Employment statusUnemployed5116Retired10Housewife279School student72University student13142Employed9831Total315100The economic situationIncome below 1 million Tomans11236Income between 1–3 million Tomans10637Income between 3–6 million Tomans6320Income above 6 million Tomans3411Total315100Source: research findingsModel  EstimationThe OLS method was used to estimate the model.Table  2.  Model estimation resultsRA                                                                The dependent variableprobabilityt-statCoefficientsVariables0.00-3.71-0.027 * * *Optimism0.0023.070.0003 * * *Wealth0.000-63.60.29 * * *Income0.418-0.81-0.017Patience0.024-26.2-0.19 * *Gender0.0222.310.23 * *Single0.0005.630.044 * * *Age0.2151.240.06Education0.00075.52.16 * * *_Cons29.13F(8,295)304Number of obs0.000Prob > F0.44R-squared0.63Root MSE0.42Adj R-squared     * The coefficient is significant at  10 % level, * * The coefficient is significant at  5 % level and *** The coefficient is significant at  1 % level.Source: research calculationsThe Brush-Pagan and VIF test show that there is no heteroskedasticity and collinearity at estimated residuals.As shown in the table, as the individual’s level of optimism increases, their degree of risk aversion decreases, which is consistent with previous research conducted by Felten and Gibson (2014) and Duhman et al. (2018). In addition, the study found that wealth has a direct and significant impact on risk aversion in Iran, which aligns with the findings of Agassi et al. (2015) and Qanbili (2016). However, this result contradicts the research conducted by Ronald and Grable (2010), and therefore, the effect of wealth on risk aversion warrants further discussion and reflection.Previous research suggests that there is a likelihood that the effect of wealth on risk aversion in Iran may be opposite to that observed in other countries. This could potentially be attributed to errors in measuring wealth In Iran, where information regarding individuals’ assets and wealth is often unclear. In this respect, the present study relied on indicators such as car and house ownership and their estimated values, which were self-reported by the participants and might be subject to bias.The study findings indicated that income has a significant and negative impact on risk aversion in Iran, which is aligned with previous research conducted by Wright (2012; 2014) and Shah et al. (2020). Moreover, it was found that gender has a significant effect on risk aversion, with females being more risk-averse than males. This finding is consistent with Banir and Newbert (2016), Hosseinnejad and Haddadi (2016), and Mohammadi-Majed (2018).The findings also revealed that age has a significantly positive impact on risk aversion in Iran, which is in line with the results of Dankers and Van Suest (1999) and Menadia et al. (2016). Finally, the results showed that time preference rate and education do not have a significant impact on risk aversion in Iran.ConclusionThis research examined the impact of several factors on individuals’ risk aversion in Iran. The investigation of the research hypotheses demonstrated that variables such as optimism and income have a significantly inverse relationship with risk aversion, with higher levels leading to decreased risk aversion. Wealth and age have a significantly positive impact on risk aversion, with higher levels leading to increased risk aversion. Furthermore, the variables of time preference rate and education were found to have no significant effect on risk aversion in Iran. The study also found that married individuals are more risk-averse than single ones, and females are more risk-averse than males.The results indicated that young people, males, and the individuals with higher incomes and lower wealth tend to accept risk more readily. The findings can provide fresh insight for investment consulting and insurance companies in Iran.